Pseudomeningocele and percutaneous intrathecal lead placement complication for spinal cord stimulator. (January 2019) - Patel, Achal; Kafka, Ben; Al Tamimi, Mazin
Highlights: Recognition of intrathecal subarachnoid electrode lead placement. Technical note for epidural lead placement. Intraoperative neuromonitoring and interrogation of the spinal cord stimulator system. Management of spinal cord stimulator intrathecal lead placement complication. Abstract: The incidence of symptomatic percutaneous intrathecal subarachnoid lead placement for spinal cord stimulator is almost an unheard of complication in the literature. We present the first case of a spinal cord stimulator implant with a complication of symptomatic intrathecal subarachnoid lead placement with a pseudomeningocele. This complication was found with myelogram and addressed by replacement with a new spinal cord stimulator implant with paddle leads instead of percutaneous leads and obliterating the pseudomeningocele tract. Technique for epidural lead placement is discussed. This case illustrates a spinal cord stimulator implant complication of intrathecal percutaneous lead placement with pseudomeningocele and its recognition and treatment involving replacement of the system while minimizing risk of postoperative cerebrospinal fluid leakage. Intraoperative neuromonitoring and interrogation of the spinal cord stimulator system during implantation are effective tools for accurate epidural lead placement.